Implementasi Fisher-Yates Shuffle dan Fuzzy Tsukamoto dalam Game Edukasi Nusantara - Karim, Khairul Insan; Chairunnisa Lamasitudju; Ryfial Azhar; Fizar Syafaat; Anisa Yulandari (Politeknik Negeri Batam, 2025)
This research introduces